THE INFLUENCE OF ENGLISH SONGS TO IMPROVE STUDENTS’ PRONUNCIATION IN TENTH GRADE OF VOCATIONAL HIGH SCHOOL - Liswanti Liswanti; Siti Sumirah (PROJECT (Professional Journal of English Education), 2018)
Pronunciation is an aspect that students in Indonesia should be known and und  erstanding how to express each word in English. To make students easier to produce something in English, the writers take English song as a media to improve students’ pronunciation. Beside of they can learn how to produce something in English language; they can gain the language or a new vocabulary.  The research used pre experimental design with one group pre test and post test design which consists of 36 students as the sample. Then the data processed by SPSS 21. And the result of this research showed significance value was .00 and it is lower that the criteria .05. It means the null hypothesis was rejected and the alternative hypothesis was accepted that English song is influence media in improving students’ pronunciation.